CoSe2 / FeSe2 as well as preparation method and application thereof
By preparing a CoSe2/FeSe2 heterojunction structure, the problem of insufficient capacity of traditional sodium-ion battery anode materials was solved, and the performance improvement of sodium-ion batteries with high capacity and long cycle life was achieved.
Patent Information
- Application Number
- CN202511449533.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-10-11
- Publication Date
- 2025-11-18
AI Technical Summary
Traditional sodium-ion battery anode materials, such as hard carbon, have a low theoretical specific capacity, making it difficult to meet the needs of large-scale energy storage scenarios, and the electrochemical performance of existing electrode materials needs to be further improved.
CoSe2/FeSe2 heterojunctions were prepared using CoFe-PBA precursors under high-temperature selenization treatment. The synergistic effect of CoSe2 and FeSe2 was utilized to form a heterojunction structure, which improved electronic conductivity and cycling stability.
A high-capacity, long-cycle-life sodium-ion battery anode material has been developed, improving the electrochemical performance and electron transfer rate of sodium-ion batteries.
Smart Images

Figure CN120964732A_ABST
Abstract
Description
TECHNICAL FIELD
[0001] The present application relates to the technical field of electrode materials, in particular to a CoSe2 / FeSe2 and a preparation method and application thereof. BACKGROUND
[0002] At present, although renewable energy such as wind energy and solar energy has been developed and utilized on a large scale, the instability of the power generation process due to the alternation of day and night, seasonal changes and regional climate differences restricts the pace of sustainable development. Under this background, the development of new energy storage technologies with high capacity, long life and low cost has become a key link to support the green transformation of energy structure. Among various energy storage technologies, sodium-ion batteries gradually enter the field of view of researchers due to their abundant resource reserves, significant cost advantage and high ionic conductivity of electrolyte. The electrochemical working mechanism of sodium-ion batteries is similar to that of lithium-ion batteries, both of which realize energy storage and release through the intercalation / deintercalation of ions between the positive and negative electrodes. This characteristic provides a theoretical basis for the rapid development of sodium-ion batteries, making them a new research direction in the field of energy storage.
[0003] The electrochemical performance of sodium-ion batteries is largely determined by the intrinsic properties of electrode materials. Optimizing the crystal structure and electronic conductivity of electrode materials can effectively improve their sodium storage activity and structural stability. Currently, traditional sodium-ion battery negative materials such as hard carbon have shown certain application potential in the laboratory stage, but their low theoretical specific capacity cannot meet the needs of large-scale energy storage scenarios. Therefore, the development of high-capacity, long-cycle and environmentally friendly negative materials has become a key breakthrough in promoting the industrialization process of sodium-ion batteries. SUMMARY
[0004] Therefore, the purpose of the present application is to provide a CoSe2 / FeSe2 and a preparation method and application thereof. The CoSe2 / FeSe2 prepared by the preparation method has excellent electrochemical performance.
[0005] The present application provides a preparation method of CoSe2 / FeSe2, comprising the following steps: mixing a cobalt cyanide aqueous solution and a soluble iron salt aqueous solution, aging to obtain a CoFe-PBA precursor; the mixing does not include a reducing agent; independently placing the CoFe-PBA precursor and selenium powder in the same calcination environment for selenization treatment to obtain the CoSe2 / FeSe2.
[0006] Preferably, the concentration of the cobalt cyanide aqueous solution is 0.05-0.15 mmol / mL; the concentration of the soluble iron salt aqueous solution is 0.00625-0.15 mmol / mL; The volume ratio of the cobalt cyanide aqueous solution and the soluble iron salt aqueous solution is 1:2.
[0007] Preferably, the cobalt cyanide in the cobalt cyanide aqueous solution is potassium cobalt cyanide and / or sodium cobalt cyanide. The soluble iron salt in the soluble iron salt aqueous solution is ferric chloride and / or ferric nitrate.
[0008] Preferably, the mixing comprises stirring after adding the cobalt cyanide aqueous solution into the soluble iron salt aqueous solution. The stirring speed is 400-600 rpm, and the stirring time is 15-45 min.
[0009] Preferably, the aging temperature is 20-25℃, and the aging time is 22-26 h.
[0010] Preferably, the CoFe-PBA precursor is located downstream of the calcination environment, and the selenium powder is located upstream of the calcination environment.
[0011] Preferably, the mass ratio of the CoFe-PBA precursor and the selenium powder is 1:(4-6).
[0012] Preferably, the selenization treatment is carried out in a protective atmosphere, and the protective atmosphere is nitrogen or argon. The selenization treatment temperature is 350-450℃, the holding time is 1.5-3.5 h, and the temperature rising rate for rising to the selenization treatment temperature is 2-6℃ / min.
[0013] The application also provides the CoSe2 / FeSe2 prepared by the preparation method.
[0014] The application also provides the application of the CoSe2 / FeSe2 as a negative electrode material in a sodium ion battery.
[0015] The application provides a preparation method of CoSe2 / FeSe2, which comprises the following steps: mixing a cobalt cyanide aqueous solution and a soluble iron salt aqueous solution, aging to obtain a CoFe-PBA precursor; the mixing does not comprise a reducing agent; and independently placing the CoFe-PBA precursor and a selenium powder in the same calcination environment for selenization treatment to obtain the CoSe2 / FeSe2. 2+ 3+ - ) by coordination bond. This structure itself has high symmetry and isotropic growth tendency, and by means of high-temperature selenization annealing treatment, a cubic morphology can be constructed to form a transition metal selenide heterostructure derived from Prussian blue analogues, and then CoSe2 / FeSe2 is prepared. CoSe2 / FeSe2 inherits the structural advantages of the CoFe-PBA precursor, which can improve the conductivity and cycle stability of the CoSe2 / FeSe2 negative electrode material. At the same time, CoSe2 / FeSe2 can also make full use of the synergistic effect of CoSe2 and FeSe2 to realize the rapid transfer of electrons in the charging and discharging process, further improving the performance of sodium ion batteries. Therefore, the method for preparing CoSe2 / FeSe2 based on the CoFe-PBA precursor in the application can further improve and improve the performance of sodium ion batteries, and the implementation of the application can provide a novel negative electrode material preparation strategy for sodium ion batteries. BRIEF DESCRIPTION OF DRAWINGS
[0016] Figure 1 XRD patterns of CoSe2 / FeSe2 described in Example 1, CoSe2 described in Comparative Example 1 and FeSe2 described in Comparative Example 2; Figure 2 SEM images of CoFe-PBA precursor (a) and CoSe2 / FeSe2 (b) described in Example 1 and EDS element distribution map of CoSe2 / FeSe2 (c); Figure 3 TEM images of CoSe2 / FeSe2 described in Example 1 under different magnifications ((a)~(b)), HRTEM image (c) and SAED image (d); Figure 4 GCD curves (a) and rate performance curves (b) of sodium ion button cells prepared by CoSe2 / FeSe2 described in Example 1, CoSe2 described in Comparative Example 1 and FeSe2 described in Comparative Example 2; Figure 5 Cycle stability curves (a) and EIS curves (b) of sodium ion button cells prepared by CoSe2 / FeSe2 described in Example 1, CoSe2 described in Comparative Example 1 and FeSe2 described in Comparative Example 2. DETAILED DESCRIPTION
[0017] The application provides a preparation method of CoSe2 / FeSe2, comprising the following steps: Mixing a cobalt cyanide aqueous solution and a soluble iron salt aqueous solution, aging to obtain a CoFe-PBA precursor; the mixing does not include a reducing agent; The CoFe-PBA precursor and selenium powder are independently placed in the same calcination environment for selenization treatment to obtain the CoSe2 / FeSe2.
[0018] In the present application, all the raw materials for preparation are commercially available products well known to those skilled in the art, unless otherwise specified.
[0019] In the present application, the aqueous solution of cobalt cyanide and the aqueous solution of soluble iron salt are mixed and aged to obtain the CoFe-PBA precursor; the mixing does not include a reducing agent.
[0020] In the present application, the concentration of the aqueous solution of cobalt cyanide is preferably 0.05-0.15 mmol / mL, more preferably 0.05 mmol / mL, 0.1 mmol / mL or 0.15 mmol / mL. In the embodiments of the present application, the concentration of the aqueous solution of cobalt cyanide can be 0.1 mmol / mL.
[0021] In the present application, the aqueous solution of cobalt cyanide is preferably prepared by mixing cobalt cyanide and water to obtain the aqueous solution of cobalt cyanide; the mixing is preferably carried out under stirring, and the stirring time is preferably 15 min. The present application does not have any special limitation on the stirring speed, which is well known to those skilled in the art and can be used to ensure that the solution is clear. The water is preferably deionized water.
[0022] In the present application, the cobalt cyanide in the aqueous solution of cobalt cyanide is preferably potassium cobalt cyanide and / or sodium cobalt cyanide, more preferably potassium cobalt cyanide.
[0023] In the present application, the cobalt cyanide serves to provide a skeleton for the formation of the CoFe-PBA precursor.
[0024] In the present application, the concentration of the aqueous solution of soluble iron salt is preferably 0.00625-0.15 mmol / mL, more preferably 0.00625 mmol / mL, 0.01 mmol / mL, 0.0125 mmol / mL, 0.025 mmol / mL, 0.05 mmol / mL, 0.075 mmol / mL, 0.1 mmol / mL, 0.125 mmol / mL or 0.15 mmol / mL. In the embodiments of the present application, the concentration of the aqueous solution of soluble iron salt can be 0.025 mmol / mL.
[0025] In the present application, the soluble iron salt in the aqueous solution of soluble iron salt is preferably ferric chloride and / or ferric nitrate, more preferably ferric chloride.
[0026] In the present application, the preparation of the aqueous solution of soluble iron salt preferably comprises mixing the soluble iron salt and water to obtain the aqueous solution of soluble iron salt; the mixing is preferably carried out under stirring, and the stirring time is preferably 15 min, and the present application does not have any special limitation on the stirring speed, and a stirring speed known to those skilled in the art can be adopted and the solution is ensured to be clear. The water is preferably deionized water.
[0027] In the present application, the volume ratio of the aqueous solution of cobalt cyanide and the aqueous solution of ferric chloride is preferably 1:2.
[0028] In the present application, the mixing preferably comprises stirring after the aqueous solution of cobalt cyanide is added into the aqueous solution of soluble iron salt; the stirring speed is preferably 400-600 rpm, and more preferably 400 rpm, 500 rpm or 600 rpm; and the time is preferably 15-45 min, and more preferably 15 min, 30 min or 45 min. In the embodiment of the present application, the stirring speed can be 500 rpm, and the time can be 30 min.
[0029] In the present application, the aging temperature is preferably 20-25℃, and more preferably 20℃, 23℃ or 25℃; and the time is preferably 22-26 h, and more preferably 22 h, 24 h or 26 h. In the embodiment of the present application, the aging temperature can be 25℃, and the time can be 24 h.
[0030] In the present application, the reaction occurring in the aging process is a coordination polymerization reaction of iron salt and cobalt cyanide.
[0031] After the aging is completed, the present application further preferably comprises sequentially carried out cleaning and drying; the cleaning preferably comprises sequentially cleaning the obtained precipitate with deionized water and ethanol, and the number of times of cleaning is preferably 4-6, and more preferably 4 times, 5 times or 6 times. In the embodiment of the present application, the number of times of cleaning can be 5 times.
[0032] In the present application, the vacuum drying temperature is preferably 50-70℃, and more preferably 50℃, 60℃ or 70℃; and the time is preferably 10-14 h, and more preferably 10 h, 12 h or 14 h. In the embodiment of the present application, the vacuum drying temperature can be 60℃, and the time can be 12 h.
[0033] In the present application, the chemical composition of the CoFe-PBA precursor preferably comprises Fe3[Co(CN)6]2, and the structure of PBA is essentially a bridging coordination polymer of "metal ion-cyanide-metal ion", and the Co 3+will serve as the "first metal center" of the PBA and will bridge to another metal ion (from a soluble metal salt) via CN - forming a characteristic backbone of "Co-CN-M" (M being another metal).
[0034] After obtaining the CoFe-PBA precursor, the CoFe-PBA precursor and selenium powder are independently placed in the same calcination environment for seleniumization treatment to obtain the CoSe2 / FeSe2.
[0035] In the present application, the CoFe-PBA precursor is preferably located downstream of the calcination environment, and the selenium powder is preferably located upstream of the calcination environment.
[0036] In the present application, the mass ratio of the CoFe-PBA precursor and the selenium powder is preferably 1:(4-6), more preferably 1:4, 1:5 or 1:6. In an embodiment of the present application, the mass ratio of the CoFe-PBA precursor and the selenium powder can be 1:5.
[0037] In the present application, the seleniumization treatment is preferably carried out in a protective atmosphere, which is preferably nitrogen or argon; the temperature of the seleniumization treatment is preferably 350-450℃, more preferably 350℃, 380℃, 400℃, 420℃ or 450℃; the holding time is preferably 1.5-3.5h, more preferably 1.5h, 2h, 2.5h, 3h or 3.5h; the heating rate for heating to the temperature of the seleniumization treatment is preferably 2-6℃ / min, more preferably 2℃ / min, 3℃ / min, 4℃ / min, 5℃ / min or 6℃ / min. In an embodiment of the present application, the seleniumization treatment is carried out in a nitrogen atmosphere, the temperature of the seleniumization treatment can be 400℃, the time can be 2h, and the heating rate can be 5℃ / min.
[0038] In the present application, the role of the selenium treatment is to convert Co and Fe in CoFe-PBA into CoSe2 and FeSe2 at high temperature, and the advantage of controlling the condition parameters of the above selenium treatment within the above range is that pure CoSe2 and FeSe2 can be prepared without generating other cobalt-based and iron-based selenides; specifically, the above selenium conditions can avoid "insufficient reaction" or "excessive reaction": too low temperature (<350℃) is easy to leave un-selenized Prussian blue analogues or free Fe impurities; too high temperature (>450℃) may generate Fe3Se4 or Co3Se4 and other by-products. The range of 350~450℃ can generate high-purity FeSe2 / CoSe2 composite target selenide, reducing the interference of impurities on performance; the matching holding time (1.5~3.5h) can make selenium fully react with Fe and Co in Prussian blue analogues, while avoiding too long time leading to selenium volatilization loss, ensuring high proportion of target phase.
[0039] After the selenium treatment is completed, the present application also preferably includes cooling, and the present application does not have any special limitation on the process of the cooling, which can be performed by using the process well known to those skilled in the art.
[0040] The present application also provides CoSe2 / FeSe2 prepared by the preparation method described in the above technical solution, and a heterojunction is formed between CoSe2 and FeSe2 in the CoSe2 / FeSe2.
[0041] The present application also provides the application of CoSe2 / FeSe2 as a negative material in a sodium ion battery, and the present application does not have any special limitation on the method of the application, which can be performed by using the method well known to those skilled in the art.
[0042] The technical solutions in the present application will be described clearly and completely in combination with the embodiments in the present application. Obviously, the described embodiments are only a part of the embodiments of the present application, rather than all the embodiments. Based on the embodiments in the present application, all the other embodiments obtained by those skilled in the art without creative labor fall within the protection scope of the present application.
[0043] Embodiment 1 5mmol of potassium cobalt cyanide (K3[Co(CN)6]) was added to 50mL of deionized water, stirred for 15min to be clear, to obtain a potassium cobalt cyanide aqueous solution; 2.5mmol of iron chloride hexahydrate (FeCl3·H2O) was added to 100mL of deionized water, stirred for 15min to be clear, to obtain an iron chloride hexahydrate aqueous solution (yellow); The cobalt potassium cyanide aqueous solution was added into the ferric chloride hexahydrate aqueous solution, stirred at 500 rpm for 30 min, aged at 25℃ for 24 h, and the precipitate was washed with deionized water and ethanol for 5 times, respectively, and then the obtained yellow precipitate was dried in a vacuum drying box at 60℃ for 12 h to obtain a CoFe-PBA precursor; The CoFe-PBA precursor and 0.4 g of selenium powder were poured into two porcelain boats, respectively, and then the porcelain boat containing the CoFe-PBA precursor was placed downstream of the tube furnace, and the porcelain boat containing the selenium powder was placed upstream of the tube furnace, and then selenization treatment was carried out at 400℃ for 2 h under a nitrogen atmosphere (the heating rate was 5℃ / min), and after natural cooling to room temperature, CoSe2 / FeSe2 was obtained.
[0044] Comparative Example 1 6 mmol of cobalt chloride hexahydrate was dissolved in 20 mL of deionized water, stirred for 15 min to obtain a cobalt chloride aqueous solution; 4 mmol of cobalt potassium cyanide was dissolved in 20 mL of deionized water, stirred for 15 min to obtain a cobalt potassium cyanide aqueous solution; The cobalt chloride aqueous solution was added into the cobalt potassium cyanide aqueous solution, stirred at 500 rpm for 30 min, aged at room temperature for 24 h, and then the precipitate was washed with deionized water and ethanol for 5 times, respectively, and then the obtained pink precipitate was dried in a vacuum drying box at 60℃ for 12 h to obtain a Co-PBA precursor; The Co-PBA precursor and 0.4 g of selenium powder were poured into two porcelain boats, respectively, and then the porcelain boat containing the Co-PBA precursor was placed downstream of the tube furnace, and the porcelain boat containing the selenium powder was placed upstream of the tube furnace, and then selenization treatment was carried out at 400℃ for 2 h under a nitrogen atmosphere (the heating rate was 5℃ / min), and after natural cooling to room temperature, CoSe2 was obtained.
[0045] Comparative Example 2 6 mmol of ferrous chloride hexahydrate was dissolved in 20 mL of deionized water, stirred for 15 min to obtain a ferrous chloride aqueous solution; 4 mmol of potassium ferricyanide was dissolved in 20 mL of deionized water, stirred for 15 min to obtain a potassium ferricyanide aqueous solution; The ferrous chloride aqueous solution was added into the potassium ferricyanide aqueous solution, stirred at 500 rpm for 30 min, aged at room temperature for 24 h, and then the precipitate was washed with deionized water and ethanol for 5 times, respectively, and then the obtained blue precipitate was dried in a vacuum drying box at 60℃ for 12 h to obtain a Fe-PBA precursor; 0.08g of the Fe-PBA precursor and 0.4g of selenium powder were poured into two ceramic boats respectively. The ceramic boat containing the Fe-PBA precursor was placed downstream of the tube furnace, and the ceramic boat containing the selenium powder was placed upstream of the tube furnace. Under a nitrogen atmosphere, the furnace was selenized at 400℃ for 2h (heating rate of 5℃ / min). After naturally cooling to room temperature, FeSe2 was obtained.
[0046] Test Example 1 Figure 1 The XRD patterns are of CoSe2 / FeSe2 described in Example 1, CoSe2 described in Comparative Example 1, and FeSe2 described in Comparative Example 2. Figure 1 It can be seen that the diffraction peaks of CoSe2 described in Comparative Example 1 correspond one-to-one with the standard diffraction peaks of cubic phase CoSe2 (PDF#53-0449), and the diffraction peaks of FeSe2 described in Comparative Example 2 correspond one-to-one with the standard diffraction peaks of FeSe2 (PDF#12-0291). For the CoSe2 / FeSe2 composite material, its diffraction peaks are located between the diffraction peaks of CoSe2 and FeSe2, indicating that the CoSe2 / FeSe2 composite material was successfully synthesized. By observing the XRD of the CoSe2 / FeSe2 composite material, it can be found that the diffraction peaks at 30.9°, 34.6°, 36.1°, 47.9° and 53.8° correspond to the (101), (111), (120), (211) and (031) crystal planes of CoSe2 and FeSe2, respectively. Figure 2 The images show SEM images of the CoFe-PBA precursor (a) and CoSe2 / FeSe2 (b) described in Example 1, as well as the EDS elemental distribution map (c) of CoSe2 / FeSe2. Figure 2 As shown in (a), the CoFe-PBA precursor has a three-dimensional cubic structure with a smooth surface, sharp edges, and exhibits a disordered stacking state, with a size between 300 and 500 nm; Figure 2 As shown in (b), compared to its precursor, CoSe2 / FeSe2 exhibits a nanoparticle morphology with a rough surface. This is because the CoFe-PBA precursor undergoes crystal decomposition and reconstruction during selenization annealing, gradually transforming from a cubic morphology into nanoparticles. The nanoparticle size of CoSe2 / FeSe2 is between 400-600 nm, slightly larger than that of the CoFe-PBA precursor; Figure 2 As shown in (c), the elemental distribution analysis diagram of the energy dispersive X-ray spectroscopy (EDS) of CoSe2 / FeSe2 shows that Co, Fe, and Se elements are uniformly distributed, further verifying the successful synthesis of CoSe2 / FeSe2. Figure 3The images shown are TEM images ((a)~(b)), HRTEM images (c), and SAED images (d) of CoSe2 / FeSe2 at different magnifications as described in Example 1. Figure 3 As shown in (a) to (b), CoSe2 / FeSe2 exhibits a nanoparticle structure with a particle size of approximately 400 nm. The surface becomes rough after selenization annealing, consistent with the structure characterized by SEM. To further confirm the existence of the heterostructure between CoSe2 and FeSe2 in CoSe2 / FeSe2, [further details are needed]. Figure 3 As shown in (c), the lattice fringes with spacings of 0.307 nm and 0.249 nm match the (011) and (120) crystal planes of CoSe2. Furthermore, the lattice fringes with spacings of 0.170 nm and 0.258 nm belong to the (031) and (111) crystal planes of FeSe2; Figure 3 As shown in (d), the concentric rings indicate that CoSe2 / FeSe2 has polycrystalline properties. The cyan diffraction rings correspond to the (200) and (311) crystal planes of CoSe2, respectively, while the red diffraction rings correspond to the (120) and (002) crystal planes of FeSe2, respectively. The characterization results of TEM and HRTEM are consistent with the XRD and EDS analysis results, proving the formation of the CoSe2 / FeSe2 heterostructure.
[0047] Test case Preparation of electrode sheet: Using CoSe2 / FeSe2 described in Example 1, CoSe2 described in Comparative Example 1, and FeSe2 described in Comparative Example 2 as active materials, the active materials, carbon black, and sodium carboxymethyl cellulose were added to water in a ratio of 7:1.5:1.5 and stirred to obtain a slurry; the slurry was drop-coated onto the surface of copper foil and vacuum dried overnight at 60°C to obtain a sodium-ion battery electrode sheet; Assembly of button batteries: The operation was carried out in an argon-filled glove box, with the water and oxygen content in the box controlled below 0.1 ppm. The assembled button battery model was CR2032. The specific assembly sequence was positive electrode shell - electrode plate - separator - sodium plate - spring plate - negative electrode shell. The separator used was Celgard 2400 separator. The electrolyte was a mixed organic solvent of diethyl carbonate and ethylene carbonate with a volume ratio of 1:1 containing 1M NaClO4, and 5 wt% fluoroethylene carbonate was added as a functional additive. The assembled sodium-ion button batteries were subjected to electrochemical performance testing: Within a potential window range of 0.01–3.0 V, the constant current charge-discharge (GCD), rate performance, and cycle performance at room temperature were characterized using a Newway battery tester. Cyclic voltammetry (CV) curves at different scan rates were measured on an electrochemical workstation (CHI660E) within the range of 0.01–10 V. 6Electrochemical impedance spectroscopy (EIS) was performed in the frequency range of 100 kHz to 0.1 Hz with an AC signal of 5 mV amplitude; Figure 4 The GCD curves (a) and rate performance curves (b) of the sodium-ion button cells prepared from the CoSe2 / FeSe2 of Example 1, the CoSe2 of Comparative Example 1 and the FeSe2 of Comparative Example 2 are shown in FIG. 1. Figure 4 As shown in (a) of FIG. 1, the discharge specific capacity of the CoSe2 of Comparative Example 1 in the first cycle was 453 mA·h·g -1 , and the discharge specific capacity in the fifth cycle was 324 mA·h·g -1 ; the discharge specific capacity of the FeSe2 of Comparative Example 2 in the first cycle was 496 mA·h·g -1 , and the discharge specific capacity in the fifth cycle was 377 mA·h·g -1 ; the discharge specific capacity of the CoSe2 / FeSe2 of Example 1 in the first cycle was 846 mA·h·g -1 , and the discharge specific capacity in the fifth cycle was 649 mA·h·g -1 , which showed that the CoSe2 / FeSe2 had better sodium-ion battery performance than the CoSe2 and the FeSe2. Figure 4 As shown in (b) of FIG. 1, the CoSe2 / FeSe2 had higher discharge specific capacity under different current densities than the CoSe2 and the FeSe2, and showed more stable rate performance. Under the current density of 0.1 A·g -1 , the discharge specific capacity of the CoSe2 / FeSe2 was 649 mA·h·g -1 (5th), under the current density of 1 A·g -1 , the discharge specific capacity of the CoSe2 / FeSe2 was 524 mA·h·g -1 (23th), and it is worth noting that when the current density returned to 0.1 A·g -1 , the discharge specific capacity of the CoSe2 / FeSe2 could reach 653 mA·h·g -1 (32nd), which showed good stable reversibility. Figure 5 The cycle stability curves (a) and EIS curves (b) of the sodium-ion button cells prepared from the CoSe2 / FeSe2 of Example 1, the CoSe2 of Comparative Example 1 and the FeSe2 of Comparative Example 2 are shown in FIG. 2. Figure 5 As shown in (a) of FIG. 2, the CoSe2 / FeSe2 of Example 1 had better cycle stability than the CoSe2 and the FeSe2. Under the current density of 0.5 A·g -1CoSe2 / FeSe2 has a larger discharge specific capacity under the current density. At the same time, CoSe2 / FeSe2 also has a relatively stable capacity retention rate, and the discharge specific capacity is 498 mA·h·g -1 after 60 charge-discharge cycles, and the capacity retention rate is as high as 95%. The above results show that the CoSe2 / FeSe2 composite material has relatively stable cycle stability; it can be seen from (b) in FIG. 6 that the charge transfer resistance of CoSe2, FeSe2 and CoSe2 / FeSe2 is 123, 268 and 60 Ω respectively, and it can be seen that CoSe2 / FeSe2 has a faster charge transfer capacity, which is beneficial to the reaction kinetics process of the sodium ion battery. Figure 5
[0048] The above only describes the preferred embodiments of the present application, and does not limit the present application in any form. It should be noted that, for ordinary skilled persons in the art, without departing from the principles of the present application, a number of improvements and refinements can be made, and these improvements and refinements should be considered as the protection scope of the present application.
Claims
1. A method for preparing CoSe2 / FeSe2, characterized in that, Includes the following steps: An aqueous solution of cobalt cyanide and an aqueous solution of soluble iron salt were mixed and aged to obtain the CoFe-PBA precursor; the mixture did not include a reducing agent. The CoFe-PBA precursor and selenium powder were placed independently in the same calcination environment for selenization treatment to obtain CoSe2 / FeSe2.
2. The preparation method according to claim 1, characterized in that, The concentration of the cobalt cyanide aqueous solution is 0.05~0.15 mmol / mL; The concentration of the soluble iron salt aqueous solution is 0.00625~0.15 mmol / mL; The volume ratio of the cobalt cyanide aqueous solution to the soluble iron salt aqueous solution is 1:
2.
3. The preparation method according to claim 2, characterized in that, The cobalt cyanide in the aqueous solution is potassium cobalt cyanide and / or sodium cobalt cyanide; The soluble iron salt in the aqueous solution of the soluble iron salt is ferric chloride and / or ferric nitrate.
4. The preparation method according to any one of claims 1 to 3, characterized in that, The mixing process includes adding an aqueous solution of cobalt cyanide to the aqueous solution of the soluble iron salt and then stirring. The stirring speed is 400~600 rpm, and the time is 15~45 min.
5. The preparation method according to claim 4, characterized in that, The aging temperature is 20~25℃ and the time is 22~26 h.
6. The preparation method according to claim 1, characterized in that, The CoFe-PBA precursor is located downstream of the calcination environment, and the selenium powder is located upstream of the calcination environment.
7. The preparation method according to claim 1 or 6, characterized in that, The mass ratio of the CoFe-PBA precursor to selenium powder is 1:(4~6).
8. The preparation method according to claim 7, characterized in that, The selenization process is carried out in a protective atmosphere, which is either nitrogen or argon. The selenization treatment temperature is 350~450℃, the holding time is 1.5~3.5h, and the heating rate to the selenization treatment temperature is 2~6℃ / min.
9. The CoSe2 / FeSe2 prepared by the preparation method according to any one of claims 1 to 8, characterized in that, A heterojunction is formed between CoSe2 and FeSe2 in the CoSe2 / FeSe2.
10. The application of the CoSe2 / FeSe2 as a negative electrode material in sodium-ion batteries according to claim 9.